Narrativas visuais e a educação pela imagem em "O dia em que me tornei mulher" de Marziyeh Meshkiny - Domingues, Ana Carolina (2023)
This work aimed to present a theoretical and filmographic discussion based on the images and allegories captured from the Iranian film “The Day I Became a Woman” by director Marziyeh Meshkiny, with the purpose of establishing a dialogue with visual education (based on some illuminations produced in the version of the Book of Kings, commissioned by Shah Tahmasp I) and cinema made by women. To this end, an analysis of the film's allegories and an interpretation of the film was made at the level of the script, extra-filmic materials and images that we consider agents based on the concept developed by Milton de Almeida (2009). Consequently, we identify how these images manifest themselves in the film and can resonate with viewers, as we understand the process of education through image as forming intelligibility of the world, memory and alterity.